Eye retinal changes under the influence of chromium ions (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Relationships between human eyes and metal ions take multiple forms. Neurotoxicity manifests as peripheral neuropathy, sensorineural hearing loss; ocular toxicity is presented as visual impairment. Regulation of heavy metal toxicity by the heat shock proteins (HSP90) and S100 family proteins has not been investigated in eye retina. The aim of our study was to investigate S100 and HSP90 expression in retina under the influence of chromium ion.Material and Methods. 36 (72 eyes) male albino rats that weighed 300-325 g were evaluated for histological and immunostainings for HSP90aa1 and S100. 18 rats of experimental group (36 eyes) got potassium bichromate (Sigma, USA) into drinking water in a dose of 0.02 mol/l. The rats of control group (18 individuals) drank usual drinking water. Animals were taken out of experiment at Days 20, 40 and 60 (first, second and third groups, respectively, six animals in each group) after the beginning of potassium bichromate introduction.Results. We noted the HSP90aa1 enzymatic activity in the control group. Induction of the enzymatic activity of HSP90aa1 was increased in the second group (89.7±3.5% P
Keywords: eye retina; chromium ion; HSP90aa1; S100